Inequality Estimations of Subclass of Univalent Functions Involving Raducanu-Orhan Operator - Manickam, Thirucheran; Kumar, Saravanan; Ramachandran, Navaneetha Krishnan; Thangamani, Stalin; Pandi, Boopathy (Journal of the Indonesian Mathematical Society, 2026)
The vast number of new papers that have been written about the univalent function in recent years shows how fascinating it is. Univalent functions are injective analytic functions, which means that they do not take the same value at various places within their domain. Univalent functions are important in complex analysis and have many uses in other areas of mathematics, physics, and engineering. These days, there is a high need for operators of normalized analytic functions, particularly differential and integral operator. Operators are widely used in numerous mathematical and scientific domains. Differential equations can be solved using these operators, which are also used to describe a wide range of physical phenomena. Many researchers have reviewed and discussed a substantial amount of material for the operators. In this work, the new subclass of univalent functions is defined by the Raducanu-Orhan differential operator. In addition, the coefficient inequalities, extreme points, integral means of inequality, and Fekte-Szego inequality for the subclass have been obtained.